2016
DOI: 10.1016/j.cpr.2015.11.002
|View full text |Cite
|
Sign up to set email alerts
|

School-based programmes to reduce and prevent substance use in different age groups: What works for whom? Systematic review and meta-regression analysis

Abstract: Our findings highlight the importance of considering a developmental perspective when designing and offering school-based prevention programmes. The various developmental stages offer different possibilities and opportunities for the reduction and prevention of substance use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
180
4
17

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 211 publications
(219 citation statements)
references
References 31 publications
6
180
4
17
Order By: Relevance
“…Three of the meta‐analyses provided information on the optimal age to deliver preventive interventions for alcohol and drugs . While these meta‐analytic findings consistently found that school‐based preventive interventions were effective in reducing alcohol and drug use, there are some inconsistencies as to their effectiveness amongst different age groups.…”
Section: Resultsmentioning
confidence: 99%
“…Three of the meta‐analyses provided information on the optimal age to deliver preventive interventions for alcohol and drugs . While these meta‐analytic findings consistently found that school‐based preventive interventions were effective in reducing alcohol and drug use, there are some inconsistencies as to their effectiveness amongst different age groups.…”
Section: Resultsmentioning
confidence: 99%
“…Traditional approaches to substance use prevention have focused on adolescents only; however, recent evidence suggests that expanding student interventions to include parenting components could markedly increase prevention effects [6-8]. This is because parents are key agents of adolescent socialization, especially in the initiation and development of substance use [9-13], and parenting interventions have been identified as critical components of effective substance use prevention programs [6,9,13,14]. Moreover, adolescent substance use is an area of substantial concern for parents, who generally want to be engaged in substance use harm prevention [15].…”
Section: Introductionmentioning
confidence: 99%
“…The program content is expert-driven, that is, evidenced-based and universal messages are applied to a generalized target audience (Dietrich et al, 2015, Newton et al, 2016. Recent studies, however, have indicated that this 'one fits all' approach might not be effective (Lee et al, 2016, Onrust et al, 2016: First, a generalized approach means that young people might not identify with the communicated message, leading to little engagement with or even rejection of the program. Second, the didactic one-way delivery of the content, while often adding to the disengagement of the target audience, additionally requires the teacher to play as the key actor to deliver these types of programs.…”
Section: Literature Alcohol Education -Exploring New Approachesmentioning
confidence: 99%
“…One way to do this is through school-based alcohol education programs, which portray the risks of drinking and providing protective strategies for young people when facing drinking situations (Lee et al, 2016). Recent studies point out that the effectiveness of alcohol education is not merely based on knowledge transfer but on student engagement achieved through the integration of interactive and context-specific components that students can identify with (Lee et al, 2016, Onrust et al, 2016). Yet these components are not considered in the current alcohol education programs because these are typically one-way didactic, delivered by teachers to students in a classroom setting (Lee et al, 2016).…”
Section: Introductionmentioning
confidence: 99%